A genetic model for the female sterility barrier between Asian and African cultivated rice species - Garavito Espejo, AM; Guyot, R.; Lozano, J.; Gavory, F; Samain, S; Panaud, O; Tohme, Joseph M.; Ghesquière, Alain; Lorieux, Mathias (Oxford University Press, 2010)
S1 is the most important locus acting as a reproductive barrier between Oryza sativa and O. glaberrima. It is a complex locus, with factors that may affect male and female fertility separately. Recently, the component causing the allelic elimination of pollen was fine mapped. However, the position and nature of the component causing female sterility remains unknown. To fine map the factor of the S1 locus affecting female fertility, we developed a mapping approach based on the evaluation of the degree of female transmission ratio distortion (fTRD) of markers. Through implementing this methodology in four O. sativa × O. glaberrima crosses, the female component of the S1 locus was mapped into a 27.8-kb (O. sativa) and 50.3-kb (O. glaberrima) region included within the interval bearing the male component of the locus. Moreover, evidence of additional factors interacting with S1 was also found. In light of the available data, a model where incompatibilities in epistatic interactions between S1 and the additional factors are the cause of the female sterility barrier between O. sativa and O. glaberrima was developed to explain the female sterility and the TRD mediated by S1. According to our model, the recombination ratio and allelic combinations between these factors would determine the final allelic frequencies observed for a given cross.